A study of ex-situ carbon mineralization under low intensity aqueous reaction - Adam Sjolund; Olivia Andrea Wrenn; Amy Tattershall; Thomas Sasser; Lisa A. Thompson; Jennifer Wade (Carbon Capture Science & Technology)
Safe, scalable and permanent options for carbon dioxide storage is essential to achieve net negative greenhouse gas emissions and limit catastrophic global warming. A benign and thermodynamically stable form of CO2 storage is a carbonate mineral. This work examined ex situ carbon mineralization of magnesium rich ultramafic and mafic rocks under previously unstudied low intensity aqueous reaction conditions (T = 25 °C, PCO2 = 80 kPa, pH = 7). Carbonate reaction extents, dissolved metals and formed carbonate phases were evaluated in experiments ranging from days to months using thermogravimetric and evolved gas analysis, dissolved elemental analysis, BET surface area, and semi-quantitative powder x-ray diffraction methods. Reaction kinetics were similar across both mineral types, with 12 % reaction extent achieved in under ten weeks. After 160 days of low intensity reaction, the ultramafic xenolith trapped 9 ± 2 wt% CO2. After 64 days of reaction, a scoriaceous picrite basalt trapped 7 ± 3 wt% CO2. Primarily amorphous magnesium carbonate was formed, with partial conversion to magnesite upon oven drying. The CO2 mineralization of abundant surface rocks under mild conditions offer potential for alternative mineralization strategies for permanent negative CO2 emissions.